2016
DOI: 10.4049/jimmunol.1502595
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Crystals Activate the Lectin Complement Pathway via Ficolin-2 and Mannose-Binding Lectin: Implications for the Progression of Atherosclerosis

Abstract: Cholesterol crystals (CC) play an essential role in the formation of atherosclerotic plaques. CC activate the classical and the alternative complement pathways, but the role of the lectin pathway is unknown. We hypothesized that the pattern recognition molecules (PRMs) from the lectin pathway bind CC and function as an upstream innate inflammatory signal in the pathophysiology of atherosclerosis. We investigated the binding of the PRMs mannose-binding lectin (MBL), ficolin-1, ficolin-2, and ficolin-3, the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 69 publications
6
41
0
Order By: Relevance
“…By the functional in vitro assay measuring C3 deposition on mannan, our study suggests that MBL-driven LP activation is associated with plaque instability. This association is further supported by the observation that MBL is present only in ulcerated plaques undergoing rupture, therefore extending previous work reporting MBL binding to intraplaque cholesterol crystals (53), clearly defining that plaque rupture is needed for MBL entry. Thus, although alternative interpretations cannot be excluded, i.e., that MBL is not consumed due to a lack of involvement in the condition, the overall data may indicate the association of MBL with plaque instability.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…By the functional in vitro assay measuring C3 deposition on mannan, our study suggests that MBL-driven LP activation is associated with plaque instability. This association is further supported by the observation that MBL is present only in ulcerated plaques undergoing rupture, therefore extending previous work reporting MBL binding to intraplaque cholesterol crystals (53), clearly defining that plaque rupture is needed for MBL entry. Thus, although alternative interpretations cannot be excluded, i.e., that MBL is not consumed due to a lack of involvement in the condition, the overall data may indicate the association of MBL with plaque instability.…”
Section: Discussionsupporting
confidence: 84%
“…As an alternative hypothesis ficolin-2, whose high intraplaque levels correlate with low plaque vulnerability, may be protective. In this case, ficolin-2 could contribute to debris clearance, in line with its function as an opsonin for phagocytosis independent of complement activation (53). …”
Section: Discussionmentioning
confidence: 99%
“…CCs can also induce either passive (physical) or regulated necrosis of the endothelial cells. They are reported to induce endothelial cell injury via complement activation [4]. Furthermore, they kill tubular epithelial cells by activating receptor-interacting serine/threonine-protein kinase 3 (RIPK3) and mixed lineage kinase domain-like (MLKL) [5, 6].…”
Section: Type 1 Crystalline Nephropathy: Renal Cholesterol Embolismmentioning
confidence: 99%
“…In our study, higher MBL plasma levels were observed in patients with cardiovascular disorders (CAD and HVD) than in the CG, in agreement with the evidence showing that high levels of circulating MBL is a risk factor for ischemic diseases, including myocardial infarction (29). The MBL protein recognizes structures exposed in altered endothelial cells, contributing to tissue damage (33,34). In acute myocardial ischemia, MBL inhibition has been shown to reduce the infarction area by promoting a reduction in neutrophil infiltration and pro-inflammatory gene expression (35).…”
Section: Discussionmentioning
confidence: 99%